Work-family enrichment and successful aging at work: The China context - Zhao, Chenhui; Ma, Huajun; Chen, Zimeng; Liu, Xiaohui (Frontiers in Psychology, 2023)
Existing research mainly analyzes the antecedents of successful aging at work from the perspective of the work field, ignoring that in the Chinese context of “familism,” the two fields of family and work permeate each other and may have an impact on successful aging at work. Thus, through a multi-time data collection approach, we obtained a sample of 338 older Chinese employees to examine the impact of work-family enrichment on successful aging at work, the mediating role of occupational future time perspective, and the moderating role of age-inclusive human resource practice. Results indicate that work-to-family enrichment was positively associated with successful aging at work through the mediation of occupational future time perspective. Family-to-work enrichment was positively associated with successful aging at work through the mediation of occupational future time perspective. In addition, age-inclusive human resource practice amplified the positive effects of work-to-family enrichment and family-to-work enrichment on occupational future time perspective. This is an exploration of successful aging at work in the Chinese context, broadening the theoretical research on successful aging at work and providing new ideas for managers on motivating older employees to achieve successful aging at work.